Multibody dynamics simulation of an all-wheel-drive motorcycle for handling and energy efficiency investigations - Griffin, J.W.; Popov, A.A. (Taylor & Francis, 2017)
It is now possible, through electrical, hydraulic or mechanical means, to power the front wheel of a motorcycle. The aim of this is often to improve performance in limit-handling scenarios including off-road low-traction conditions and on-road high-speed cornering. Following on from research into active torque distribution in 4-wheeled vehicles, the possibility exists for efficiency improvements to be realised by reducing the total amount of energy dissipated as slip at the wheel–road contact. This paper presents the results of an investigation into the effect that varying the torque distribution ratio has on the energy consumption of the two-wheeled vehicle. A 13-degree of freedom multibody model was created, which includes the effects of suspension, aerodynamics and gyroscopic bodies. SimMechanics, from the MathWorks_, is used for automatic generation of equations of motion and time-domain simulation, in conjunction with MATLAB and Simulink. A simple driver model is used to control the speed and yaw rate of the motorcycle. The handling characteristics of the motorcycle are quantitatively analysed, and the impact of torque distribution on energy consumption is considered during straight line and cornering situations. The investigation has shown that only a small improvement in efficiency can be made by transferring a portion of the drive torque to the front wheel. Tyre longevity could be improved by reduced slip energy dissipation.